2021
DOI: 10.1038/s41467-021-23113-z
|View full text |Cite
|
Sign up to set email alerts
|

16p11.2 deletion is associated with hyperactivation of human iPSC-derived dopaminergic neuron networks and is rescued by RHOA inhibition in vitro

Abstract: Reciprocal copy number variations (CNVs) of 16p11.2 are associated with a wide spectrum of neuropsychiatric and neurodevelopmental disorders. Here, we use human induced pluripotent stem cells (iPSCs)-derived dopaminergic (DA) neurons carrying CNVs of 16p11.2 duplication (16pdup) and 16p11.2 deletion (16pdel), engineered using CRISPR-Cas9. We show that 16pdel iPSC-derived DA neurons have increased soma size and synaptic marker expression compared to isogenic control lines, while 16pdup iPSC-derived DA neurons s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 96 publications
3
38
1
Order By: Relevance
“…To comprehensively investigate the maturity of spinal motor neurons, we utilized the CMOS-based HD-MEA platform, which is a high-throughput and high-resolution system containing 26,400 electrodes and 1,024 simultaneous recording channels (Muller et al, 2015; Sundberg et al, 2021; Yuan et al, 2020). We first scanned and analyzed the entire HD-MEA electrode array to examine spontaneous neural activities during spinal motor neuron differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…To comprehensively investigate the maturity of spinal motor neurons, we utilized the CMOS-based HD-MEA platform, which is a high-throughput and high-resolution system containing 26,400 electrodes and 1,024 simultaneous recording channels (Muller et al, 2015; Sundberg et al, 2021; Yuan et al, 2020). We first scanned and analyzed the entire HD-MEA electrode array to examine spontaneous neural activities during spinal motor neuron differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Together, the notable similarities and many differences in transcriptomic alterations between brain regions, peripheral tissues and human neuronal cells indicate that the CNV dosage changes of the same set of genes have impacts, both in terms of biological processes disrupted and in terms of the genes most significantly altered within those processes, that are context-specific. The importance of cellular context is reinforced by differences in the functional impact of the 16p11.2 CNV in our iNs (reduced numbers of neurites and branchpoints and electrical activity due to both deletion and duplication) compared to dopaminergic neurons (larger soma and hyperexcitability due to deletion and increased number of neurites due to duplication) derived from the same hiPSCs (Sundberg et al, 2021). Consequently, it is likely that multiple CNV genes and consequently disrupted biological processes contribute to the phenotypic features of the 16p11.2 RGD, potentially through a combination of different effects in different contributing cell types.…”
Section: Discussionmentioning
confidence: 96%
“…We performed replication analysis using the published raw transcriptomic data of cellular models derived from hiPSC with 16p11.2del, including cortex neurons (Roth et al, 2020), dopaminergic neuron (Sundberg et al, 2021), and cortical organoids (1M and 3M refers to 1 Month and 3M organoid) (Urresti et al, 2021). For the neuron cell data (Roth et al, 2020), DAVID gene enrichment analysis showed MAPK3 was involved in 60 out of the 73 enrichment categories.…”
Section: Mapk3 Emerges As Driver Signal Related To Abnormal Developme...mentioning
confidence: 99%